The complement receptor 3 (CD11b/CD18) agonist Leukadherin-1 suppresses human innate inflammatory signalling. (26th July 2016) - Roberts, A L; Fürnrohr, B G; Vyse, T J; Rhodes, B
Summary: Complement receptor 3 (CR3, CD11b/CD18) is a multi-functional receptor expressed predominantly on myeloid and natural killer (NK) cells. The R77H variant of CD11b, encoded by the ITGAM rs1143679 polymorphism, is associated robustly with development of the autoimmune disease systemic lupus erythematosus (SLE) and impairs CR3 function, including its regulatory role on monocyte immune signalling. The role of CR3 in NK cell function is unknown. Leukadherin-1 is a specific small-molecule CR3 agonist that has shown therapeutic promise in animal models of vascular injury and inflammation. We show that Leukadherin-1 pretreatment reduces secretion of interferon (IFN)-γ, tumour necrosis factor (TNF) and macrophage inflammatory protein (MIP)-1β by monokine-stimulated NK cells. It was associated with a reduction in phosphorylated signal transducer and activator of transcription (pSTAT)-5 following interleukin (IL)-12 + IL-15 stimulation ( P < 0·02) and increased IL-10 secretion following IL-12 + IL-18 stimulation ( P < 0·001). Leukadherin-1 pretreatment also reduces secretion of IL-1β, IL-6 and TNF by Toll-like receptor (TLR)-2 and TLR-7/8-stimulated monocytes ( P < 0·01 for all). The R77H variant did not affect NK cell response to Leukadherin-1 using ex-vivo cells from homozygous donors; nor did the variant influence CR3 expression by these cell types, in contrast to a recent report. These data extend our understanding of CR3 biology by demonstrating that activation potently modifies innate immune inflammatory signalling, including a previously undocumented role in NK cell function. We discuss the potential relevance of this to the pathogenesis of SLE. Leukadherin-1 appears to mediate its anti-inflammatory effect irrespective of the SLE-risk genotype of CR3, providing further evidence to support its evaluation of Leukadherin-1 as a potential therapeutic for autoimmune disease.